Bacteriophage endolysin Ply113 as a potent antibacterial agent against polymicrobial biofilms formed by enterococci and Staphylococcus aureus - Wang, Jing; Liang, Siyu; Lu, Xiaofeng; Xu, Qiu; Zhu, Yao; Yu, Shenye; Zhang, Wanjiang; Liu, Siguo; Xie, Fang (Frontiers in Microbiology, 2023)
Antibiotic resistance in Enterococcus faecium, Enterococcus faecalis, and Staphylococcus aureus remains a major public health concern worldwide. Furthermore, these microbes frequently co-exist in biofilm-associated infections, largely nullifying antibiotic-based therapy. Therefore, it is imperative to develop an efficient therapeutic strategy for combating infections caused by polymicrobial biofilms. In this study, we investigated the antibacterial and antibiofilm activity of the bacteriophage endolysin Ply113 in vitro. Ply113 exhibited high and rapid lytic activity against E. faecium, E. faecalis, and S. aureus, including vancomycin-resistant Enterococcus and methicillin-resistant S. aureus isolates. Transmission electron microscopy revealed that Ply113 treatment led to the detachment of bacterial cell walls and considerable cell lysis. Ply113 maintained stable lytic activity over a temperature range of 4-45°C, over a pH range of 5.0-8.0, and in the presence of 0-400 mM NaCl. Ply113 treatment effectively eliminated the mono-species biofilms formed by E. faecium, E. faecalis, and S. aureus in a dose-dependent manner. Ply113 was also able to eliminate the dual-species biofilms of E. faecium-S. aureus and E. faecalis-S. aureus. Additionally, Ply113 exerted potent antibacterial efficacy in vivo, distinctly decreasing the bacterial loads in a murine peritoneal septicemia model. Our findings suggest that the bacteriophage endolysin Ply113 is a promising antimicrobial agent for the treatment of polymicrobial infections.